Interaction of Lead and Bacterial Lipids - Tornabene, Thomas G. (1975)
Studies on the interaction of lead with lipid components indicate that individual lipids do not provide specific stable binding sites for lead, but that natural membrane lipid mixtures may simply provide an environment suitable for nucleation of lead.